Funkcja użyteczności — krytyka - Rapka, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The utility function has long been the main tool used by many economists due to the mathematization of economics. Some textbooks on mathematical economics state that the application of mathematics in economics imposes greater rigor, precision, and transparency of assumptions, not significantly different from the non-mathematical method. When analyzing utility function, it can be noticed that its application influences the economic analysis by imposing certain behaviors onpeople and giving them a mechanical character, primarily by introducing a constant relationship between the goods or goals considered by the person. For this reason, it is almost impossible to takei nto account the real uncertainty in theoretical research, which overly mechanizes the description of decision-making and economic processes.
Keywords: użyteczność; teoria wyboru; teoria wartości; metodologia